The Efficacy of Plea Bargaining in the Promotion of the Criminal Justice: Pros and Cons - Frank Nyesigire (Uganda Christian University, 2025)
The efficiency of plea bargaining in the criminal justice system is examined critically in this study with reference to its operational, legal, and ethical issues. As a mechanism primarily used to expedite criminal cases and alleviate court congestion, plea bargaining has been a central component of most justice systems around the world. However, greater reliance on it throws grave doubts regarding fairness, voluntariness, and undermining fundamental rights. The study explores the historical development of plea bargaining, its statutory basis in various jurisdictions, and the different forms it can take, i.e., charge bargaining, sentence bargaining, and fact bargaining. It also explores the theoretical justifications which lend legitimacy to its practice, i.e., efficiency, resource management, and promoting judicial economy. However, it also refers to criticism that frames plea bargaining as a procedure that may compel defendants to waive their right to a fair trial under unfair bargaining terms and with limited understanding of the consequences. Methodologically, the study adopts a mixed approach: doctrinal analysis to examine statutory provisions and case law governing plea bargaining, and qualitative data gathered through questionnaires with legal professionals such as judges, prosecutors, and defense lawyers. This allows for a thorough understanding of the way plea bargaining works in practice and whether it is effective in its desired outcomes. The findings indicate that although plea bargaining can significantly reduce delays and expenses of trials, it may also compromise the ideals of justice by prioritizing expediency over the discovery of truth. Inequalities in legal representation, the discretion of prosecutors, and the limited supervision of judges often result in unequal outcomes. The research underscores the need for stricter procedural protections, greater transparency, and more standardized practices to ensure that plea bargains are truly voluntary, informed, and equitable. Lastly, the study argues that while plea bargaining is a good and precious institution in modern criminal justice systems, its efficacy must be quantified not only on the criterion of efficiency but also in respect for the rule of law and protection of individual rights. The article demands reforms aimed to enhance accountability, reduce coercion, and unify legal protections for defendants in plea agreements.